The evolution of the generalized differentiated services architecture and the changing role of the Internet engineering task force - Günter Knieps (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2013)
The changing role of the Internet Engineering Task Force (IETF) standard setting process from designing and implementing the best effort TCP/IP protocol as a universal standard towards a platform for dealing with the increasing need for variety in the design of a Quality of Service (QoS) differentiated traffic management architecture is demonstrated. The IETFs contributions to a flexible open transmission architecture able to supply the required transmission qualities for the different applications provide the relevant pillars towards a Generalized Differentiated Service (DiffServ) architecture. Furthermore, the role of entrepreneurial traffic management within the Generalized DiffServ architecture and the division of labor between the IETF and entrepreneurial traffic management is analyzed. Within the umbrella architecture of Generalized DiffServ with the potential to combine basic elements of QoS differentiated traffic architectures a flexible framework for entrepreneurial traffic quality differentiation strategies is evolving. Its basic characteristic is market driven network neutrality with all applications bearing the opportunity costs of their required traffic capacities. As a consequence an artificial market split between best effort TCP and managed services would conflict with the integrated service approach of the IETF. Finally, the implementation of Generalized DiffServ via Next Generation networks is considered.
Keywords: 330